Novel evidence for retinoic acid‐induced G (Rig‐G) as a tumor suppressor by activating p53 signaling pathway in lung cancer. Issue 9 (2nd August 2020) - Sun, Junjun; Wang, Xuan; Liu, Wenfang; Ji, Ping; Shang, Anquan; Wu, Junlu; Zhou, Hao; Quan, Wenqiang; Yao, Yiwen; Yang, Yibao; Gu, ChenZheng; Sun, Zujun; et al.
Abstract: Lung cancer is one of most common malignancies worldwide. We have previously identified retinoic acid‐induced gene G (Rig‐G) as a tumor suppressor in not only acute promyelocytic leukemia, but also in other solid tumors. However, the clinical significance of Rig‐G and the underlying mechanism(s) for its biological function in lung cancer remain largely unexplored. Herein, we first compared the expression of Rig‐G between lung cancer (n = 138) and normal tissues (n = 23), from public‐available data sets and our patient cohort. We further analyzed the correlation of Rig‐G expression with key clinico‐pathological features and survival outcomes in a multi‐site clinical cohort of 300 lung cancer patients. Functional studies for Rig‐G were performed in cell lines, and an animal model to support clinical findings. We found that Rig‐G was frequently downregulated in lung cancer tissues and cell lines, and correlated with poor prognosis in lung cancer patients. Overexpression of Rig‐G led to significantly reduced cell growth and suppressed migration in A549 and NCI‐H1944 cells, accompanied by reduced epithelial‐mesenchymal transition. Likewise, restoration of Rig‐G in Lewis lung carcinoma cells permitted development of fewer cancer metastases versus controls in an animal model. Gene expression profiling results identified p53 pathway as a key downstream target of Rig‐G, and p53 inhibition by pifithrin‐α caused abrogation of tumor‐suppressive effects of Rig‐G in lung cancer. In conclusion, we, for the first time, have identified Rig‐G as a novel and important tumor suppressor, which may serve as a potential therapeutic target for restoring p53 expression in lung cancer patients.